2017
DOI: 10.1097/aln.0000000000001434
|View full text |Cite|
|
Sign up to set email alerts
|

Vasopressin versus Norepinephrine in Patients with Vasoplegic Shock after Cardiac Surgery

Abstract: Background Vasoplegic syndrome is a common complication after cardiac surgery and impacts negatively on patient outcomes. The objective of this study was to evaluate whether vasopressin is superior to norepinephrine in reducing postoperative complications in patients with vasoplegic syndrome. Methods This prospective, randomized, double-blind trial was conducted at the Heart Institute, University of Sao Paulo, Sao Paulo, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
204
2
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(222 citation statements)
references
References 23 publications
1
204
2
15
Order By: Relevance
“…Vasodilatory shock (vasoplegia) has become a common occurrence, particularly with the widespread use of angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers . In a recent RCT of patients with vasoplegic shock (defined as mean arterial pressure <65 mm Hg resistant to fluid challenge and cardiac index >2.2 L/min per m 2 ) after cardiac surgery, vasopressin was associated with lower incidence of severe AKI (stages 2 and 3) and RRT use, although, again, study limitations prevent recommendation and further research is needed …”
Section: Resultsmentioning
confidence: 99%
“…Vasodilatory shock (vasoplegia) has become a common occurrence, particularly with the widespread use of angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers . In a recent RCT of patients with vasoplegic shock (defined as mean arterial pressure <65 mm Hg resistant to fluid challenge and cardiac index >2.2 L/min per m 2 ) after cardiac surgery, vasopressin was associated with lower incidence of severe AKI (stages 2 and 3) and RRT use, although, again, study limitations prevent recommendation and further research is needed …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our work indicates that reducing the time of CPB decreases the risk of developing vasoplegia. For patients who have already developed vasoplegia, a randomized clinical trial revealed that those who went on to receive vasopressin instead of norepinephrine had fewer postoperative complications . Furthermore, a literature review regarding the use of methylene blue (MB) as a treatment for vasoplegia confirmed that MB is safe if used within the recommended dosage and is useful for treating vasoplegia, although its benefit is time‐dependent .…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that one of the mechanisms of genesis of AF could be an excess of catecholamines or an increased sensitivity to them [19]. Vasopressin could also trigger AF [20], although it may have a lower ability to induce arrhythmias in critical patients [21, 22]. In our study, no patient in vasopressin use developed AF (Table 2 and Figure 1).…”
Section: Discussionmentioning
confidence: 55%